The Effect of Recombinant Growth Hormone Administration on Bonylip Barb (Osteochilus vittatus) Fry at Diferent Stocking Densities. - Carman, Odang; Maharani, Adinda; Alimuddin; Rahmi, Kurnia Anggraini (Program Studi Budidaya Perairan Universitas Mataram, 2025)
The nilem fish (Osteochilus vittatus) has high economic value, but its growth rate is relatively slow. One potential solution to accelerate its cultivation period is the use of recombinant growth hormone (rGH). This study aimed to evaluate the effect of oral administration of rGH derived from Epinephelus lanceolatus (rElGH) on the growth rate of nilem fish juveniles at different stocking densities. A completely randomized design with three replications was used in this study. Juvenile fish with an average length of 4.43±0.03 cm and weight of 0.96±0.03 g were reared in aquaria measuring 100 × 50 × 50 cm with a water height of 20 cm for 30 days. The fish were fed commercial feed containing 31–33% protein, with rElGH-supplemented feed given to satiation twice daily (at 08:00 and 16:00) during the first seven days, followed by regular feed without rElGH. The best production performance was obtained in the R30 treatment group (30 fish per 100 L with rElGH), with an absolute weight gain (AWG) of 3.4 g, a survival rate of 98.89%, and a specific growth rate (SGR) of 4.8% per day, indicating that nilem fish given rElGH grew faster.